Nastanek, zbirke in vizije kustodiata za socialno kulturo v Slovenskem etnografskem muzeju - Židov, Nena (Etnolog. Nova vrsta (Ljubljana), 2003)
The Department of Social Culture was established in the Slovene Ethnographic Museum in the 1970s. Its origin was brought about by several earlier thematic research projects and the presence of collected objects as well as collections. The article presents the department's existing collections and the guidelines for its future activities.
Keywords: Slovenski etnografski muzej; Ljubljana; muzejske zbirke; socialna kultura; način življenja; Slovenia; Slovenija